Ramulus Mori (Sangzhi) alkaloids ameliorate high-fat diet induced obesity in rats by modulating gut microbiota and bile acid metabolism - Shang, Xin; Fu, Yu; Wang, Ying; Yan, Shuxun (Frontiers in Endocrinology, 2024)
ObjectiveThe objective of this study is to investigate the ability of Ramulus Mori (Sangzhi) alkaloid tablets (SZ-A) to ameliorate obesity and lipid metabolism disorders in rats subjected to a high-fat diet (HFD) through metagenomics, untargeted lipidomics, targeted metabolism of bile acid (BA), and BA pathways, providing a novel perspective on the management of metabolic disorders.MethodsIn this research, HFD-fed rats were concurrently administered SZ-A orally. We measured changes in body weight (BW), blood lipid profiles, and liver function to assess therapeutic effects. Liver lipid status was visualized through H&E and Oil Red O. Gut microbiota composition was elucidated using metagenomics. The LC-MS-targeted metabolomics approach was utilized to define the fecal BA profiles. Furthermore, the lipid metabolomics of adipose tissue samples was investigated using an LC-MS analysis platform. The expression levels of the BA receptor were determined by western blotting. Additionally, serum insulin (INS), glucagon-like peptide-1 (GLP-1), and inflammatory cytokines were quantified using an ELISA kit. The integrity of the colonic epithelial barrier was assessed using immunofluorescence.ResultsSZ-A notably decreased BW and blood lipid levels in obese rats while also alleviating liver injury. Additionally, SZ-A reduced the serum levels of leptin (LEP), INS, and GLP-1, indicating its potential to modulate key metabolic hormones. Most notably, SZ-A substantially improved gut microbiota composition. Specifically, it reshaped the gut microbiota structure in HFD-fed rats by increasing the relative abundance of beneficial bacteria, such as Bacteroides, while decreasing the populations of potentially harmful bacteria, such as Dorea and Blautia. At the BA level, SZ-A decreased the levels of harmful BAs, including hyodeoxycholic acid (HDCA), deoxycholic acid (DCA), 12-keto lithocholic acid (12-KLCA), lithocholic acid (LCA), and muricholic acid (MDCA). Between the model group and SZ-A, 258 differentially abundant metabolites were detected, with 72 upregulated and 186 downregulated. Furthermore, these BAs are implicated in the activation of the FXR-FGF15 and TGR5-GLP-1 pathways in the intestine. This activation helps to alleviate HFD-fed intestinal inflammation and restore intestinal barrier damage by modulating inflammatory cytokines and bolstering the intestinal barrier’s capabilities.ConclusionsOur findings indicate that SZ-A effectively modulates BW, serum lipid profiles, and liver function in HFD-fed rats. Moreover, SZ-A exerts a positive influence on inflammatory cytokines, thereby mitigating inflammation and promoting the restoration of the intestinal barrier. Significantly, our research indicates that adjusting the gut microbiome and BA levels could serve as an effective approach for both preventing and treating obesity and related metabolic dyslipidemia.